Feasibility Study Business Development Ajwa Archery Collaboration and Community Based - Arif, Maftuhin; Djatmiko, Budi (Economic: Journal Economic and Business, 2022)
Currently, sports are not only limited to physical demands to improve health and fitness but also become a place for meetings, friendships, building business relationships, to a more serious direction, namely achievement and prestige. Therefore, the sports sector becomes a timeless business opportunity and can target various groups regardless of age. This study aims to conduct a feasibility study on the business development plan of Ajwa Archery which is located in Pangkalpinang City, Bangka Belitung Islands Province. The study was developed on aspects of decoupling and SWOT, business management, marketing, production/operations, human resource management, as well as finance and investment. The results of the study show that with improvements and innovations in several related aspects that are optimistic that they can be executed, the results of calculations and financial analysis will show that conditions are feasible to be realized